Adaptive stochastic methods : in computational mathematics and mechanics - Arsenʹev, D. G. (Dmitriĭ Germanovich), 1963-; Ivanov, Vladimir M.; Korenevskiĭ, M. L. (Maksim Lʹvovich) (De Gruyter, 2018)
"This monograph is devoted to developing adaptive stochastic methods of computational mathematics with the use of adaptively controlled computational procedures. We consider the base ideas of the algorithms, ways to synthesise them, and analyse their properties and efficiency while evaluating multidimensional integrals and solving integral equations of the theory of elasticity and the theory of heat conduction. The key feature of the approaches and results presented in this book consists of a comprehensive analysis of mechanisms of utilisation of adaptive control in statistical evaluation procedures, which makes them converge much faster. This book is intended for all students of numerical methods, mathematical statistics, and methods of statistical simulation, as well as for specialists in the fields of computational mathematics and mechanics"--Page v